Method for modifying and finishing fabric

By modifying polyamide fibers with protease under acidic conditions and finishing with polyalkylsiloxane hydrosol, the problem of not lasting modification effect in the prior art is solved, and the durability and efficiency of fiber surface modification are improved.

CN120138984APending Publication Date: 2025-06-13WUJIANG FUHUA WEAVING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510232153.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

When modifying polyamide fibers, the modification effect is not long-lasting, and the amide bond hydrolysis rate is slow, which affects the hydrophilicity and dyeing properties of the fibers.

Method used

The fibers were surface modified with protease under acidic conditions to form carboxyl groups and form microscopic rough structures. Then, polyalkylsiloxane hydrosol was used for finishing, which improved the durability of the finishing effect through the dual effects of valence bonding and mechanical nail anchoring.

Benefits of technology

The durability and efficiency of fiber surface modification are improved, the hydrophilicity and dyeing properties of the fiber are improved, and the fixing strength of the finishing agent is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005293519970000131
    Figure BDA0005293519970000131
  • Figure BDA0005293519970000141
    Figure BDA0005293519970000141
  • Figure HDA0005293520130000011
    Figure HDA0005293520130000011
Patent Text Reader

Abstract

The invention discloses a method for modifying and finishing a fabric, which is characterized by comprising the following steps: adjusting the pH value of polyalkyl siloxane hydrosol to 6-7 by using an alkaline agent, finishing the modified fabric by using a padding method, and then washing and drying to prepare the fabric. According to the method for modifying and finishing the fabric, the polyalkyl siloxane hydrosol is adopted for finishing after the fibers are modified, and the polyamide fibers are easy to hydrolyze under an acidic condition, so that the use performance of the fabric is influenced. The pH value of the silicon dioxide sol is adjusted to 6-7, so that rapid condensation of sol particles is not caused, and the fiber strength is not obviously influenced. A mixture of anionic sodium dodecyl benzene sulfonate and nonionic twin-80 is adopted as a surfactant, the strength of sodium dodecyl benzene sulfonate micelles is enhanced, meanwhile, the viscosity of the hydrosol can be effectively reduced, and then the stability of the hydrosol and the uniformity of the particle size are improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the application date of October 29, 2021, application number 2021112726387, and invention title "A Fabric and Its Preparation Method". Technical Field

[0002] The present invention relates to the technical field of textiles, and specifically relates to a method for modifying and finishing fabrics. Background Art

[0003] With the development of technology and the improvement of living standards, people are increasingly pursuing an environmentally friendly, healthy, and safe life, and functional textiles have gradually become the trend of today's textile development. Functional textiles refer to textiles with some special functions different from the inherent properties of ordinary textiles. According to different properties and uses, functional textiles can be mainly divided into hygiene and environmental protection functions, protective functions, medical and health care functions, thermal and moisture comfort functions, etc.

[0004] The sol-gel technology refers to making compounds containing highly active chemical components generate functionalized thin films with different components on the surface of the substrate through solutions, sol-gels, and heat treatments, so as to improve various functional characteristics of textiles such as physical and mechanical properties (such as wear resistance), antistatic properties, anti-adhesion properties, and flame retardancy. Among them, polyalkylsiloxane hydrosol refers to a reactive functional material formed by the hydrolysis and condensation reactions of alkylsiloxanes, which can generate functionalized thin films on the fiber surface through valence bond binding and silicon hydroxyl groups (Si-OH), thereby endowing textiles with functional characteristics.

[0005] When using polyalkylsiloxane to modify polyamide fibers, not only the amount of polyalkylsiloxane fixed is reduced due to the surface hydrophobicity of the fibers, but also the durability of the modification effect is affected due to the small number of surface active reaction groups on the fibers. Theoretical analysis shows that constructing a rough structure and generating active reactive groups on the surface of polyamide fibers through modification is one of the effective methods to improve the modification effect of polyalkylsiloxane.

[0006] Currently, the main methods for modifying the surface of polyamide fibers include concentrated acid or concentrated alkali hydrolysis methods (such as the relevant content disclosed in patents with application numbers 201010218397.3, 202010654281.8, 202010654275.2, etc.), plasma methods, and electron beam irradiation methods. Among them, the acid or alkali hydrolysis method often causes serious damage to the fiber strength due to difficult-to-control treatment conditions, and the plasma method and electron beam radiation method have not been well applied in large-scale production at present.

[0007] Bioenzymes are widely used in textile finishing due to their high efficiency, specificity, and mild treatment conditions. Literature reports that proteases, cutinases, amidases, and lipases can hydrolyze the amide bonds (-COONH-) in polyamides, but the catalytic activity of enzymes towards polyamide polymers is not high, the treatment time is too long, and the improvement of related properties such as the hydrophilicity and dyeability of modified fibers is not satisfactory. In addition, due to surface erosion, bioenzyme treatment can also cause certain damage to fiber strength.

[0008] For example, in a Chinese invention patent application with the application number 200580018511.5 and the title "Method for Modifying Polyamide", a method of applying protease to the modification of polyamide is disclosed. However, the content disclosed in the application mainly includes increasing the content of carboxyl groups (-COOH) on the surface of polyamide fibers through protease modification, thereby improving the hydrophilicity and dyeability of the fibers; and in the treatment method disclosed in the application, only salts (sodium phosphate and sodium citrate) are used to adjust the pH value of the enzyme reaction solution, and no other additives are added. The disadvantage is that the hydrolysis rate of amide bonds is slow. To obtain a sample with a significantly increased carboxyl content, it often takes 24 hours or longer for the reaction. Summary of the Invention

[0009] In view of this, in order to overcome the defects of the prior art, the purpose of the present invention is to provide a method for preparing a fabric that can more persistently and effectively maintain its characteristics.

[0010] To achieve the above purpose, the present invention adopts the following technical solutions:

[0011] A method for preparing a fabric, comprising the following steps: surface-modifying the fibers of the fabric with protease under acidic conditions; then preparing a polyalkylsiloxane hydrosol; finishing the modified fabric with the prepared polyalkylsiloxane hydrosol to obtain the fabric; the surfactant used in the process of preparing the polyalkylsiloxane hydrosol is a mixture composed of sodium dodecylbenzenesulfonate and twain-80. The fibers used in the fabric are aliphatic polyamide fibers.

[0012] According to some preferred embodiments of the present invention, the acidic condition is a pH value of 3.0 - 4.0, preferably 3.5.

[0013] According to some preferred embodiments of the present invention, a surfactant is used in the process of modifying the fibers of the fabric, and the surfactant is a non-ionic surfactant, preferably nonylphenol polyoxyethylene ether and aliphatic polyoxyethylene ether surfactants.

[0014] According to some preferred embodiments of the present invention, a buffer solution is used in the process of modifying the fibers of the fabric. The buffer solution is a mixture composed of 0.1 - 0.3 mol / L of disodium hydrogen phosphate and 0.05 - 0.2 mol / L of citric acid. Preferably, the buffer solution is a mixture composed of 0.2 mol / L of disodium hydrogen phosphate and 0.1 mol / L of citric acid in a volume ratio of 3:7, so as to maintain the pH value of the system at about 3.5.

[0015] The principle of fiber surface modification is as follows: Modifying the fiber surface, carboxyl groups (-COOH) that can react with the silanol groups (-Si-OH) on the surface of silica sol particles are generated through the hydrolysis of amide bonds (-COONH-), and at the same time, a microscopic rough structure is formed on the fiber surface through erosion, and the durability of the finishing effect is improved through the dual actions of mechanical nail anchoring and valence bond binding; the optimal application pH value for acid protease to modify the surface of polyamide fibers is about 3.5, and both acidity and protease can produce a synergistic effect during the process of hydrolyzing the amide bond (-COONH-) in the molecular structure of polyamide fibers to generate amino groups (-NH 2 ) and carboxyl groups (-COOH); adjusting the pH with a buffer solution can effectively neutralize the carboxyl groups (-COOH) generated during the modification process, so that the pH value of the system is always maintained at about 3.5 to ensure the highest effectiveness of the protease; the hydrolysis of amide bonds by organic acids is milder than that of inorganic strong acids, and the conditions are easy to control; adding a non-ionic surfactant can improve the wettability of the fiber surface, accelerate the swelling of the fiber, and then improve the spreading of the bio-enzyme treatment solution on the fiber surface, and improve the modification efficiency by increasing the effective contact area between the bio-enzyme and the fiber surface.

[0016] According to some preferred embodiments of the present invention, the pH value of deionized water is adjusted to 3.0 - 4.0 with a buffer solution, and then a surfactant and protease are added. The dosage of the surfactant is 1 - 1.5 times the critical micelle concentration (CMC), and the concentration of protease in the system is 0.02 - 2.0 g / mL; the fabric is treated under the condition of a bath ratio of 1:10 - 35, and then the fabric is washed and dried.

[0017] The non-ionic surfactant added in the present invention when protease modifies polyamide fibers can not only improve the wettability of the fiber, enhance the swelling performance of the fiber, increase the effective contact area between the protease and the fiber surface, and improve the treatment efficiency. At the same time, the main purpose of the present invention is to generate more carboxyl groups on the fiber surface through protease modification and form a microscopic rough structure, and when finishing with a silica sol-based antibacterial agent, the dual actions of valence bond binding and mechanical nail anchoring are combined to improve the fixing strength of the finishing agent on the fiber surface.

[0018] In some embodiments of the present invention, the specific steps for surface modification of fibers are as follows: Adjust the pH value of 1 L of deionized water to 3.5 with 20 mL of buffer solution, then add a surfactant and 0.2 - 2.0 g of protease. The dosage of the surfactant is 1 - 1.5 times that of CMC. Treat the fabric at 40 °C for 2 - 6 h with a bath ratio of 1∶30. After treatment, inactivate at 60 °C for 10 min, take out the fabric, wash it with water and then dry it.

[0019] According to some preferred implementation aspects of the present invention, the protease is papain. The optimal application pH value of papain is 3.0 - 4.0. The acidity of this pH value will not have an obvious impact on fiber damage and can produce a synergistic effect with the action of the biological enzyme.

[0020] According to some preferred implementation aspects of the present invention, the surfactant is a mixture composed of sodium dodecylbenzenesulfonate and twain - 80 with a mass ratio of 1∶0.1 - 0.3.

[0021] According to some preferred implementation aspects of the present invention, the preparation of the polyalkylsiloxane hydrosol includes the following steps: Add hydrochloric acid to deionized water, then add a surfactant and an antifoaming agent, stir to fully dissolve and mix the surfactant, add alkylsiloxane while stirring. After the alkylsiloxane is added, continue to stir and heat up to 40 - 60 °C, and react for 30 - 60 min under stirring conditions to obtain the polyalkylsiloxane hydrosol.

[0022] In some embodiments of the present invention, the specific steps for the preparation of the polyalkylsiloxane hydrosol are as follows: Under the condition of 25 - 30 °C, add 3 - 6 mL of hydrochloric acid to 1 L of deionized water, then add 1 - 2 g of surfactant and 0.1 - 0.3 g of antifoaming agent, stir at a speed of 300 r / min to fully dissolve sodium dodecylbenzenesulfonate, adjust the stirring speed to 600 - 1000 r / min, and add 20 - 40 g of alkylsiloxane while stirring within 5 - 10 min. After the alkylsiloxane is added, continue to stir for 60 - 90 min, then heat up at a heating rate of 1 - 2 °C / min to 40 - 60 °C, and react for 30 - 60 min under stirring conditions to obtain the polyalkylsiloxane hydrosol.

[0023] The principle of this step is: Use a mixture of anionic sodium dodecylbenzenesulfonate and non - ionic twain - 80 as the surfactant. The reason is that the addition of twain - 80 will not change the charge amount of the hydrosol system, but can enhance the strength of the sodium dodecylbenzenesulfonate micelles, and at the same time can effectively reduce the viscosity of the hydrosol, thereby improving the stability of the hydrosol and the uniformity of the particle size; the addition of the antifoaming agent can effectively avoid the generation of foam by the surfactant under high - speed stirring conditions, thereby avoiding affecting the dispersibility of the alkylsiloxane and affecting the final effect.

[0024] The preferred alkylsiloxane is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, γ-aminopropyltriethoxysilane.

[0025] According to some preferred implementation aspects of the present invention, an antibacterial agent is further added during the preparation process of the polyalkylsiloxane hydrosol, and the antibacterial agent is a chitosan / micron silver composite antibacterial agent.

[0026] In some embodiments of the present invention, the preparation method of the hydrosol with antibacterial function is as follows: Add a surfactant with a mass concentration of 0.1% and an antifoaming agent with a mass concentration of 0.01% to a hydrochloric acid deionized aqueous solution with a mass concentration of 0.46%, stir at a speed of 300 r / min at a temperature of 25°C for 60 min. After the sodium dodecylbenzenesulfonate is fully dissolved, add a chitosan / micron silver composite antibacterial agent with a mass ratio of 15% to the alkylsiloxane, and continue to stir for 60 min to disperse the antibacterial agent evenly. Add an alkylsiloxane with a mass concentration of 4% within 5 min under the stirring condition of 600 r / min. After the alkylsiloxane is added, continue to stir for 60 min, then heat up to 60°C at a heating rate of 2°C / min, and react for 30 min under the stirring condition to obtain SiO 2 Hydrosol-based chitosan / micron silver composite antibacterial agent. The mass concentration in the present invention is the mass concentration of the corresponding substance in the formed solution, rather than the original concentration of the added substance.

[0027] In some embodiments of the present invention, the preparation of the chitosan / micron silver composite antibacterial agent includes the following steps:

[0028] 1) Prepare a chitosan solution: Add chitosan with a mass concentration of 2-5% and acetic acid with a mass concentration of 1.0-2.0% to 200 mL of deionized water. The degree of deacetylation of the chitosan used is ≥90%.

[0029] 2) Prepare a micron silver dispersion: Add 0.1-0.2% of sodium dodecylbenzenesulfonate and 2-5 mL of ethanol to 50 mL of deionized water, stir at a speed of 300 r / min. After the sodium dodecylbenzenesulfonate is completely dissolved, add micron silver with a mass of 5-10% of the chitosan while stirring.

[0030] 3) Preparation of the composite antibacterial agent: Under the condition of 25 - 30 °C, stir at a speed of 600 r / min, and slowly add the micron-sized elemental silver dispersion into the chitosan solution within 10 - 20 min. After adding, continue stirring for 120 - 240 min, precipitate the crude chitosan / micron-sized elemental silver composite antibacterial agent with a centrifuge, then wash it 3 - 5 times with deionized water, and obtain the chitosan / micron-sized elemental silver composite antibacterial agent by suction filtration.

[0031] In some embodiments of the present invention, the preparation of the micron-sized elemental silver includes the following steps: Under the condition of 25 - 30 °C, add polyvinylpyrrolidone with a mass concentration of 0.5 - 1.0% and a reducing agent with a mass concentration of 1 - 2% into 200 mL of deionized water, stir at a speed of 300 r / min. After the polyvinylpyrrolidone and the reducing agent are completely dissolved, adjust the pH value of the reaction solution to 3 - 4 with an acetic acid - sodium acetate buffer solution. Under the condition of stirring, slowly add silver nitrate with a mass concentration of 2 - 5% within 5 - 10 min. After adding, continue stirring for 10 - 20 min, then heat up to 40 - 50 °C at a speed of 1 - 2 °C / min, carry out a constant-temperature reaction for 30 - 60 min, precipitate the crude micron-sized elemental silver with a centrifuge, then wash it 3 - 5 times with deionized water, and obtain the micron-sized elemental silver by suction filtration, with a particle size of 1 - 20 μm.

[0032] The reducing agent used in the preparation process of the micron-sized elemental silver is one or a composite of two of sodium citrate and ascorbic acid.

[0033] According to some preferred embodiments of the present invention, the finishing of the modified fabric includes the following steps: Adjust the pH value of the polyalkylsiloxane hydrosol to 6 - 7 with an alkali agent, and finish the modified fabric by padding, then wash it with water and dry it to make the fabric.

[0034] According to some preferred embodiments of the present invention, the alkali agent refers to a sodium hydroxide solution with a mass concentration of 4 - 8 g / L.

[0035] In some embodiments of the present invention, the steps of finishing the modified fabric with polyalkylsiloxane are specifically as follows: Under the condition of 25 - 30 °C, adjust the pH value of the polyalkylsiloxane hydrosol to 6 - 7 with an alkali agent, and finish the modified polyamide fabric by two-bath padding, with a liquor pickup rate of 60 - 100%. Then dry it at a temperature of 80 - 90 °C for 2 - 5 min, and then cure it at a temperature of 140 - 160 °C for 3 - 6 min, wash it with water, and finally dry it at a temperature of 80 - 100 °C to make the multifunctional polyamide fabric.

[0036] The principle of this step is as follows: Polyamide fibers are prone to hydrolysis under acidic conditions, which will affect the service performance of fabrics. Adjusting the pH value of the silica sol to 6 - 7 will neither cause the rapid condensation of sol particles nor have an obvious impact on fiber strength.

[0037] The present invention also provides a fabric prepared by the preparation method described above.

[0038] Due to the adoption of the above technical solutions, compared with the prior art, the advantages of the present invention are as follows: In the method for modifying and finishing the fabric of the present invention, after modifying the fibers, polyalkylsiloxane hydrosol is used for finishing. Polyamide fibers are prone to hydrolysis under acidic conditions, which will affect the service performance of fabrics. Adjusting the pH value of the silica sol to 6 - 7 will neither cause the rapid condensation of sol particles nor have an obvious impact on fiber strength; using a mixture of anionic sodium dodecylbenzenesulfonate and nonionic twain - 80 as a surfactant can enhance the strength of sodium dodecylbenzenesulfonate micelles, and at the same time can effectively reduce the viscosity of the hydrosol, thereby improving the stability and particle size uniformity of the hydrosol. Brief Description of the Drawings

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for use in the description of the embodiments. Obviously, the following - described drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0040] Figure 1 It is the microscopic magnified view of the original polyamide fiber used in the preferred embodiment of the present invention;

[0041] Figure 2 It is the microscopic magnified view of the polyamide fiber after bio - enzyme modification in the preferred embodiment 1 - 1 of the present invention;

[0042] Figure 3 It is the control picture of the antibacterial effect of the fabrics prepared in the preferred embodiment 3 - 1 of the present invention and Comparative Examples 1 - 4 to 1 - 7. Detailed Embodiments

[0043] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0044] Example 1-1 Fiber Surface Modification

[0045] Adjust the pH value of 1 L of deionized water to the optimal application value of 3.5 for protease with 20 mL of buffer solution, then add 1.0 g of protease and 1.2 CMC nonylphenol polyoxyethylene ether, and treat at 40 °C for 3 h with a liquor ratio of 1:30. After treatment, inactivate at 60 °C for 10 min, take out the fabric, wash it with water, and dry it.

[0046] Example 1-2 Fiber Surface Modification

[0047] Adjust the pH value of 1 L of deionized water to the optimal application value of 3.5 for protease with 20 mL of buffer solution, then add 1.5 g of protease and 1.2 CMC nonylphenol polyoxyethylene ether, and treat at 40 °C for 2 h with a liquor ratio of 1:35. After treatment, inactivate at 60 °C for 10 min, take out the fabric, wash it with water, and dry it.

[0048] Example 1-3 Fiber Surface Modification

[0049] Adjust the pH value of 1 L of deionized water to the optimal application value of 3.5 for protease with 20 mL of buffer solution, then add 1.0 g of protease and 1.2 CMC nonylphenol polyoxyethylene ether, and treat at 40 °C for 3 h with a liquor ratio of 1:25. After treatment, inactivate at 60 °C for 10 min, take out the fabric, wash it with water, and dry it.

[0050] Example 2-1 Preparation of Hydrogel with Antibacterial Function

[0051] 1. Preparation of Micron Silver

[0052] At 25 °C, add polyvinylpyrrolidone with a mass concentration of 0.7% and a reducing agent with a mass concentration of 1% to 200 mL of deionized water, stir at a speed of 300 r / min. After the polyvinylpyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with acetic acid-sodium acetate buffer solution. Under stirring conditions, slowly add silver nitrate with a mass concentration of 3% within 8 min. After adding, continue stirring for 15 min, then heat up to 40 °C at a rate of 1.5 °C / min, and carry out a constant-temperature reaction for 50 min. Precipitate the silver by centrifugation, then wash it 5 times with deionized water, and obtain micron silver by suction filtration.

[0053] 2. Preparation of Chitosan / Micron Silver Composite Antibacterial Agent

[0054] Chitosan solution: Add chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% to 200 mL of deionized water.

[0055] Micron silver dispersion: Add 0.15% surfactant and 3 mL ethanol to 50 mL deionized water, stir at a speed of 300 r / min. After the sodium dodecylbenzenesulfonate is completely dissolved, add micron silver with a mass of 6% of the chitosan while stirring.

[0056] Under the condition of 25 °C, stir at a speed of 600 r / min, and slowly add the micron silver dispersion to the chitosan solution within 10 min. After adding, continue to stir for 150 min, precipitate the silver by centrifuge, wash it 5 times with deionized water, and filter to obtain the chitosan / micron silver composite antibacterial agent.

[0057] 3. SiO 2 Preparation of silica sol-based antibacterial agent

[0058] Add a surfactant with a mass concentration of 0.1% and an antifoaming agent with a mass concentration of 0.01% to a hydrochloric acid deionized water solution with a mass concentration of 0.46%. Stir at a speed of 300 r / min at a temperature of 25 °C for 60 min. After the sodium dodecylbenzenesulfonate is fully dissolved, add the chitosan / micron silver composite antibacterial agent with a mass ratio of 15% to the alkylsiloxane, and continue to stir for 60 min to disperse the antibacterial agent evenly. Add methyltrimethoxysilane with a mass concentration of 4% within 5 min under the stirring condition of 600 r / min. After adding the precursor, continue to stir for 60 min, then heat up to 60 °C at a heating rate of 2 °C / min, and react for 30 min under stirring to obtain SiO 2 Silica sol-based antibacterial agent. The surfactant is a mixture of sodium dodecylbenzenesulfonate and twain-80 with a mass ratio of 1:0.2.

[0059] Preparation of the hydrogel with antibacterial function in Example 2-2

[0060] 1. Preparation of micron silver

[0061] Under the condition of 25 °C, add polyvinylpyrrolidone with a mass concentration of 0.5% and a reducing agent with a mass concentration of 1.5% to 200 mL deionized water, stir at a speed of 300 r / min. After the polyvinylpyrrolidone and the reducing agent are completely dissolved, adjust the pH of the reaction solution to 3-4 with an acetic acid-sodium acetate buffer solution. Under the stirring condition, slowly add silver nitrate with a mass concentration of 5% within 8 min. After adding, continue to stir for 15 min, then heat up to 40 °C at a rate of 1.5 °C / min, keep the temperature constant for 30 min, precipitate the silver by centrifuge, wash it 5 times with deionized water, and filter to obtain micron silver.

[0062] 2. Preparation of chitosan / micron silver composite antibacterial agent

[0063] Chitosan solution: Add chitosan with a mass concentration of 3% and acetic acid with a mass concentration of 1.0% to 200 mL of deionized water.

[0064] Micron silver dispersion: Add 0.15% surfactant and 3 mL of ethanol to 50 mL of deionized water, stir at a speed of 300 r / min. After sodium dodecylbenzenesulfonate is completely dissolved, add micron silver with a mass 10% of that of chitosan to the solution while stirring.

[0065] Under the condition of 25 °C, stir at a speed of 600 r / min, slowly add the micron silver dispersion to the chitosan solution within 10 min. After adding, continue to stir for 200 min, precipitate the silver by centrifugation, wash it with deionized water 5 times, and obtain the chitosan / micron silver composite antibacterial agent by suction filtration.

[0066] 3. SiO 2 Preparation of hydrogel-based antibacterial agent

[0067] Add a surfactant with a mass concentration of 0.16% and an antifoaming agent with a mass concentration of 0.016% to a 0.5% hydrochloric acid deionized water solution. Stir at a speed of 300 r / min at a temperature of 25 °C for 60 min. After sodium dodecylbenzenesulfonate is fully dissolved, add the chitosan / micron silver composite antibacterial agent with a mass ratio of 20% to alkylsiloxane, and continue to stir for 90 min to disperse the antibacterial agent evenly. Add propyltrimethoxysilane with a mass concentration of 4% within 5 min under the stirring condition of 600 r / min. After adding the precursor, continue to stir for 60 min, then heat up to 40 °C at a heating rate of 1.5 °C / min, and react for 30 min under the stirring condition to obtain SiO 2 Hydrogel-based antibacterial agent. The surfactant is a mixture of sodium dodecylbenzenesulfonate and twain-80 with a mass ratio of 1:0.3.

[0068] Preparation of hydrogel with antibacterial function in Example 2-3

[0069] 1. Preparation of micron silver

[0070] At 25 °C, 0.7% by mass of polyvinylpyrrolidone and 1% by mass of a reducing agent were added to 200 mL of deionized water, and the mixture was stirred at a speed of 300 r / min. After the polyvinylpyrrolidone and the reducing agent were completely dissolved, the pH of the reaction solution was adjusted to 3 - 4 with an acetic acid - sodium acetate buffer solution. Under stirring conditions, 4% by mass of silver nitrate was slowly added within 10 min. After addition, stirring was continued for 15 min, and then the temperature was raised to 40 °C at a rate of 1.5 °C / min and the reaction was carried out at a constant temperature for 40 min. The elemental silver was precipitated by a centrifuge and then washed 5 times with deionized water, and micron-sized elemental silver was obtained by suction filtration.

[0071] 2. Preparation of chitosan / micron-sized elemental silver composite antibacterial agent

[0072] Chitosan solution: 3% by mass of chitosan and 1.0% by mass of acetic acid were added to 200 mL of deionized water.

[0073] Micron-sized elemental silver dispersion: 0.1% by mass of a surfactant and 3 mL of ethanol were added to 50 mL of deionized water, and the mixture was stirred at a speed of 300 r / min. After sodium dodecylbenzenesulfonate was completely dissolved, micron-sized elemental silver with a mass 8% of that of chitosan was added while stirring.

[0074] At 25 °C, the mixture was stirred at a speed of 600 r / min, and the micron-sized elemental silver dispersion was slowly added to the chitosan solution within 10 min. After addition, stirring was continued for 150 min. The elemental silver was precipitated by a centrifuge and then washed 5 times with deionized water, and the chitosan / micron-sized elemental silver composite antibacterial agent was obtained by suction filtration.

[0075] 3. SiO 2 Preparation of SiO

[0076] 0.13% by mass of a surfactant and 0.013% by mass of an antifoaming agent were added to an aqueous solution of 0.46% by mass hydrochloric acid in deionized water. The mixture was stirred at a speed of 300 r / min at a temperature of 25 °C for 60 min. After sodium dodecylbenzenesulfonate was fully dissolved, the chitosan / micron-sized elemental silver composite antibacterial agent with a mass ratio of 20% to alkylsiloxane was added, and stirring was continued for 60 min to disperse the antibacterial agent evenly. 4% by mass of alkylsiloxane (the mass ratio of methyltrimethoxysilane to propyltrimethoxysilane was 3:1) was added within 5 min under stirring at 600 r / min. After the precursor was added, stirring was continued for 60 min, and then the temperature was raised to 40 °C at a rate of 2 °C / min and the reaction was carried out under stirring conditions for 40 min to obtain SiO 2 hydrocolloid-based antibacterial agent. The surfactant was a mixture of sodium dodecylbenzenesulfonate and twain-80 with a mass ratio of 1:0.1.

[0077] Examples 2-1 to 2-3 provide a preparation method of a multifunctional composite antibacterial finishing agent, which has the following advantages: simple process, stable and easy-to-control process parameters; excellent antibacterial effect of the antibacterial finishing agent; having active groups that can form valence bonds with the fiber surface, and the antibacterial effect of the finished fabric is persistent; the finishing agent can endow the finished fabric with good antibacterial and bacteriostatic properties, water repellency and soft handfeel at the same time.

[0078] Preparation of the fabric in Example 3-1

[0079] The preparation method of the multifunctional fabric in this example specifically includes the following steps:

[0080] (1) Fiber surface modification treatment: Modify the polyamide fabric by using the fiber surface modification method in Example 1-1;

[0081] (2) Preparation of the composite antibacterial finishing agent: Prepare the SiO 2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent by using the preparation method in Example 2-1.

[0082] (3) Polyalkylsiloxane finishing of the modified fabric: Under the condition of 25 °C, adjust the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) to 6-7 with an alkali agent, and use the two-dip and two-roll method to finish the polyamide fabric modified in step (1), with a liquor pickup rate of 80%. Then dry it at 80 °C for 2 min, cure it at 140 °C for 3 min, wash it with water, and finally dry it at 80 °C to make a multifunctional polyamide fabric.

[0083] Preparation of the fabric in Example 3-2

[0084] The preparation method of the multifunctional fabric in this example specifically includes the following steps:

[0085] (1) Fiber surface modification treatment: Modify the polyamide fabric by using the fiber surface modification method in Example 1-2;

[0086] (2) Preparation of the composite antibacterial finishing agent: Prepare the SiO 2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent by using the preparation method in Example 2-2.

[0087] (3) Modification of the fabric with polyalkylsiloxane: Under the condition of 25°C, use an alkali agent to adjust the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) to 6 - 7. Use the two-dip and two-roll method to finish the modified polyamide fabric in step (1), with a liquor pickup rate of 80%. Then dry it at 80°C for 2 min, and then cure it at 140°C for 3 min, wash it with water, and finally dry it at 80°C to make a multifunctional polyamide fabric.

[0088] Preparation of the fabric in Example 3 - 3

[0089] The preparation method of the multifunctional fabric in this example specifically includes the following steps:

[0090] (1) Fiber surface modification treatment: Modify the polyamide fabric using the fiber surface modification method in Example 1 - 3;

[0091] (2) Preparation of the composite antibacterial finishing agent: Prepare the SiO 2 hydrosol-based chitosan / micron elemental silver composite antibacterial agent using the preparation method in Example 2 - 3.

[0092] (3) Modification of the fabric with polyalkylsiloxane: Under the condition of 25°C, use an alkali agent to adjust the pH value of the polyalkylsiloxane hydrosol-based antibacterial agent in step (2) to 6 - 7. Use the two-dip and two-roll method to finish the modified polyamide fabric in step (1), with a liquor pickup rate of 80%. Then dry it at 80°C for 2 min, and then cure it at 140°C for 3 min, wash it with water, and finally dry it at 80°C to make a multifunctional polyamide fabric.

[0093] Examples 3 - 1 to 3 - 3 provide a preparation method of a multifunctional polyamide fabric, which has the following advantages: The process is simple, and the process parameters are stable and easy to control; The fabric has excellent hydrophobicity, antistatic property and comfortable hand feeling at the same time; The antibacterial functional characteristics of the fabric are persistent and it has good wash resistance.

[0094] Comparative Example 1 - 1

[0095] The difference between this comparative example and Example 1 - 1 is that: In the fiber surface modification method of this comparative example, when using protease for modification, no non-ionic surfactant is added. The remaining steps of this comparative example are basically the same as those of Example 1 - 1.

[0096] Comparative Example 1 - 2

[0097] The difference between this comparative example and Example 1 - 1 is that: In the fiber surface modification method of this comparative example, the pH value of the control system is 4.2. The remaining steps of this comparative example are basically the same as those of Example 1 - 1.

[0098] Comparative Examples 1-3

[0099] The difference between this comparative example and Example 1-1 is that: in the fiber surface modification method of this comparative example, the pH value of the control system is 2.8. The remaining steps of this comparative example are basically the same as those of Example 1-1.

[0100] Comparative Examples 1-4

[0101] The difference between this comparative example and Example 3-1 is that: in this comparative example, when preparing the SiO 2 hydrocolloid-based antibacterial agent, micron elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent. The remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0102] Comparative Examples 1-5

[0103] The difference between this comparative example and Example 3-1 is that: in this comparative example, when preparing the SiO 2 hydrocolloid-based antibacterial agent, nano elemental silver is used to replace the chitosan / micron elemental silver composite antibacterial agent. The remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0104] Comparative Examples 1-6

[0105] The difference between this comparative example and Example 3-1 is that: in this comparative example, when preparing the SiO 2 hydrocolloid-based antibacterial agent, chitosan is used to replace the chitosan / micron elemental silver composite antibacterial agent. The remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1.

[0106] Comparative Examples 1-7

[0107] The difference between this comparative example and Example 3-1 is that: in this comparative example, when preparing the SiO 2 hydrocolloid-based antibacterial agent, chitosan / nano elemental silver composite antibacterial agent is used to replace the chitosan / micron elemental silver composite antibacterial agent. The remaining steps of this comparative example are basically the same as those of Example 2-1 and Example 3-1. Among them, the nano elemental silver is prepared by a conventional method, and then the chitosan / nano elemental silver composite antibacterial agent is prepared by using Step 2 in Example 2-1.

[0108] Comparative Examples 1-8

[0109] The difference between this comparative example and Example 3-1 is that: in the fabric preparation method of this comparative example, Step (1) in Example 3-1 is not implemented, that is, the fiber surface is not modified in this comparative example. The remaining steps of this comparative example are basically the same as those of Example 3-1.

[0110] Results and Discussion

[0111] (1) Testing the effect of fiber surface modification

[0112] For the fiber modified fabrics prepared in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-3, the following terminal carboxyl group content and weight loss rate were measured. Among them, the testing method for the terminal carboxyl group content was carried out according to the method described on page 13 of the patent specification with the application number 200580018511.5 and the title of "Method for Modifying Polyamide"; the weight loss rate was measured by the constant temperature dry weight method. The specific method was as follows: The fabric was placed in an oven at 105-110 °C and dried to a constant weight balance (about 4 h), and then weighed with an analytical balance. The weight loss rate = (W 0 -W 1 ) / W 0 ×100%, where: W 0 is the weight of the fabric before treatment; W 1 is the weight of the fabric after treatment. The test results of the modification effect are shown in Table 1 below:

[0113] Table 1 Test results of fiber surface modification effect

[0114] Terminal carboxyl content (mmol / kg) Weight loss rate / % Example 1-1 95.2 1.2±0.3 Example 1-2 101.1 1.3±0.3 Example 1-3 97.2 1.2±0.3 Comparative Example 1-1 88.6 1.1±0.3 Comparative Example 1-2 83.5 0.8±0.3 Comparative Example 1-3 84.3 2.0±0.3

[0115] The test results in Table 1 show that the terminal carboxyl group content of the fibers treated in the examples is significantly higher than that of the fibers treated in the comparative examples. The terminal carboxyl group content of the fibers treated in Example 1-1 is higher than that of the fibers treated in Comparative Example 1-1, indicating that the addition of the non-ionic surfactant increases the hydrolysis rate of the amide bond. The terminal carboxyl group content of the fibers treated in Example 1-2 is the highest because the mass concentration of the protease in Example 1-2 is high, and the effective contact opportunity between the fiber and the bio-enzyme per unit time is more.

[0116] The terminal carboxyl group content of the fibers treated in Comparative Example 1-1 is higher than that of the fibers treated in Comparative Examples 1-2 and 1-3. This may be because the pH value of the treatment solution in Comparative Example 1-1 is within the optimal active pH value range of papain, so the terminal carboxyl group content of the fibers treated in Comparative Example 1-1 is the highest among the fibers treated in the comparative examples. In addition, compared with Comparative Examples 1-2 and 1-3, the terminal carboxyl group content of the fibers treated in Comparative Example 1-3 is slightly higher, probably because the pH value of the treatment solution in Comparative Example 1-3 is lower (pH = 2.8), and the stronger the acidity, the worse the stability of the amide bond. The weight loss rate of the fibers treated in the comparative examples shows that the weight loss of the fibers is caused by the combined action of acidity and protease. The terminal carboxyl group content of the fibers treated in Comparative Example 1-1 is the largest, but the weight loss rate is not the largest, indicating that the hydrolysis of the amide bond by protease is milder than that under acidic conditions and will not cause the polyamide molecular chain to break into small molecules and detach from the fiber main body in a short time.

[0117] (2) Antibacterial rate test

[0118] AsFigure 3 As shown, the antibacterial rates of the fabrics prepared in Examples 3-1 to 3-3 and Comparative Examples 1-4 to 1-7 were tested; the test method for the antibacterial rate refers to GB / T 20944.1-2007 Evaluation of antibacterial properties of textiles - Part 1: Agar plate diffusion method. The test results of the antibacterial rate are shown in Table 2 below:

[0119] Table 2 Test results of antibacterial rate

[0120]

[0121] The test results in Table 2 show that when the alkyl polysiloxane hydrosol is used as the matrix, the antibacterial property of chitosan is the worst (Comparative Example 1-6), and the antibacterial properties of micron silver (Comparative Example 1-4) and nano silver (Comparative Example 1-5) both reach 100%. Silver can significantly improve the antibacterial property of chitosan. The antibacterial properties of chitosan / micron silver (Examples 3-1, 3-2 and 3-3) are similar to those of silver (Comparative Examples 1-4 and 1-5), and are better than those of chitosan / nano silver (Comparative Example 1-7). Reason analysis: Chitosan is a porous material. When silver is combined with chitosan, part of the silver is adsorbed on the surface of chitosan, and the other part is adsorbed into the pores of chitosan. The smaller the particle size of silver, the greater the probability of adsorption into the pores of chitosan. And silver is a contact-type antibacterial agent, so the antibacterial property of chitosan / micron silver (Examples) is better than that of chitosan / nano silver (Comparative Example 1-7).

[0122] (3) Durability test

[0123] The following tests were carried out on the fabrics prepared in Examples 3-1 to 3-3 and Comparative Example 1-8: antibacterial rate, hand feeling and static contact angle. Among them, the test method for the antibacterial rate refers to GB / T 20944.1-2007 Evaluation of antibacterial properties of textiles - Part 1: Agar plate diffusion method; the hand feeling was tested by touching with hands; the static contact angle was tested using an OCA50Micro type full-automatic single fiber contact angle measuring instrument (Dataphysics Instruments GmbH, Germany). The washing method refers to GB / T 8629-2017 Textiles - Home laundering and drying procedures for testing. The test results are shown in Table 3 below:

[0124] Table 3 Test results

[0125]

[0126] The test results in Table 3 show that when using the polyalkylsiloxane hydrosol-based antibacterial agent to finish the polyamide fabric, the antibacterial property, hand feeling and static contact angle of the fabrics prepared in Comparative Examples 1-8 (without bioenzyme modification) are similar to those of the fabrics prepared in Examples 3-1 (bioenzyme modified). However, after 20 or 50 washes, the performance of the fabrics prepared in Examples 3-1 is significantly better than that of the fabrics prepared in Comparative Examples 1-8. The main reason is that bioenzyme modification can not only form carboxyl groups (-COOH) that form valence bonds with silanol groups (Si-OH) on the fiber surface, but also form a microscopic rough structure. The rough structure has a mechanical meshing effect with the polyalkylsiloxane coating, thereby improving the durability of the finishing effect.

[0127] Table 3 also shows that changing the polyalkylsiloxane precursor (i.e., the specific substance of alkylsiloxane) can endow the finished fabric with different hand feelings (Examples 3-1, 3-2 and 3-3), but does not affect the antibacterial property (i.e., antibacterial rate) and hydrophobicity (i.e., static contact angle), nor has an obvious impact on the durability of the finishing effect.

[0128] In the preparation method of the present invention, when performing fiber modification, the pH of the system is controlled to be about 3.5. At this time, the acidity has a synergistic effect with the erosion of the polyamide fiber surface by protease. The eroded fiber can not only effectively increase its adsorption amount of polyalkylsiloxane hydrosol, but also improve the durability of the effect through mechanical nail anchoring and valence bond binding (-COOH on the fiber and -OH on the polyalkylsiloxane). At the same time, the film formed by polyalkylsiloxane can make up for the damage to the fiber strength caused by the erosion effect.

[0129] In the fabric preparation method of the present invention, by controlling the pH value of the system to be always 3.0-4.0 and adding a non-ionic surfactant, the protease can efficiently play its role in modifying the fiber, resulting in a synergistic effect; at the same time, a microscopic rough structure is formed on the fiber surface through the erosion effect, and the durability of the finishing effect is improved through the dual effects of mechanical nail anchoring and valence bond binding; a mixture of anionic sodium dodecylbenzenesulfonate and non-ionic twain-80 is used as the surfactant to enhance the strength of the sodium dodecylbenzenesulfonate micelle, and at the same time can effectively reduce the viscosity of the hydrosol, thereby improving the stability and particle size uniformity of the hydrosol.

[0130] The above embodiments are only for illustrating the technical concept and characteristics of the present invention, and the purpose is to enable those familiar with this technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for modifying and finishing a fabric, characterized in that, it comprises the following steps: adjusting the pH value of the polyalkylsiloxane hydrosol to 6 - 7 with an alkali agent, finishing the modified fabric by padding, then washing with water and drying to make a fabric.

2. The method according to claim 1, characterized in that, the alkali agent refers to a sodium hydroxide solution with a mass concentration of 4 - 8 g / L.

3. The method according to claim 1, characterized in that, the pick-up rate of the padding is 60 - 100%, and after padding, it is dried at a temperature of 80 - 90 °C for 2 - 5 min, and then baked at a temperature of 140 - 160 °C for 3 - 6 min.

4. The method according to claim 1, characterized in that, the polyalkylsiloxane hydrosol is prepared by the following steps: adding hydrochloric acid into deionized water, then adding a surfactant and an antifoaming agent, stirring to fully dissolve and mix the surfactant, adding alkylsiloxane while stirring, after the alkylsiloxane is added, continue to stir and heat up to 40 - 60 °C, and react for 30 - 60 min under stirring to obtain the polyalkylsiloxane hydrosol.

5. The method according to claim 4, characterized in that, the surfactant is a mixture composed of sodium dodecylbenzenesulfonate and twain - 80 with a mass ratio of 1∶0.1 - 0.

3.

6. The method according to claim 4, characterized in that, the alkylsiloxane is one or more selected from methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, γ - aminopropyltriethoxysilane.

7. The method according to claim 1, characterized in that, the modification is to modify the fibers of the fabric with protease under acidic conditions, and ensure that the pH value of the system is always 3.0 - 4.0 during the modification process.

8. The method according to claim 7, characterized in that, the acidic condition is a pH value of 3.0 - 4.

0.

9. The method according to claim 7, characterized in that, a buffer solution is used during the process of modifying the fibers of the fabric, and the buffer solution is a mixture composed of disodium hydrogen phosphate with a concentration of 0.1 - 0.3 mol / L and citric acid with a concentration of 0.05 - 0.2 mol / L.

10. The method according to claim 7, characterized in that, the protease is papain.

11. The method according to claim 7, characterized in that, an antibacterial agent is also added during the preparation process of the polyalkylsiloxane hydrosol, the antibacterial agent is a chitosan / micron elemental silver composite antibacterial agent, and the particle size of the micron elemental silver is 1 - 20 μm.

Citation Information

Patent Citations

  • Method for preparing nylon surface grafting chitosan hydrophilic antibiotic material

    CN101880403A

  • A method for preparing a durable antibacterial polyamide fabric

    CN111809385B

  • Manufacturing method of efficient antibacterial polyamide fabric

    CN111826952A

  • Method for modifying polyamide

    CN1965124A